Composite salt grouting material and preparation method thereof
By using the combination of fast-hardened sulfoaluminate cement and ordinary silicate cement and the simplified preparation process of other materials, the problems of complex preparation process, high cost and high construction difficulty of composite salt grouting materials are solved, and low cost is achieved , simplified process and high-performance composite salt grouting materials.
Patent Information
- Application Number
- CN202411597224.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing composite salt grouting materials have problems such as high complexity, high cost and high construction difficulty in the preparation process, which limits their wide application in engineering.
It adopts a combination of fast-hardened sulfur aluminate cement and ordinary silicate cement, combining fly ash, slag micro powder, nano silicon powder, calcium chloride, graphene oxide, titanium dioxide and modified methyl cellulose and other materials. Composite salt grouting materials are prepared by a simplified stirring and standstill process.
It realizes low cost, simplified preparation process and convenient construction of composite salt grouting materials, significantly improves the fluidity, strength, durability and self-healing ability of the materials, and is suitable for a variety of engineering grouting applications.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a composite salt grouting material and a preparation method thereof. Background Art
[0002] In modern construction projects, grouting materials play a vital role in filling and sealing gaps, cracks and holes in structures. These materials ensure the integrity and stability of building structures, prevent the penetration of water and harmful substances, and thus extend the service life of buildings. Although traditional grouting materials, such as cement-based grouting materials and chemical grouting materials, can meet basic needs in many cases, they still have obvious limitations in terms of durability, impermeability, and resistance to freeze-thaw cycles. Especially under extreme climatic conditions, such as high temperature, low temperature, and high humidity, the performance of these traditional grouting materials will be significantly reduced. For example, in high temperature environments, grouting materials may experience premature aging and strength loss; in low temperature conditions, the materials may become brittle and lose elasticity; and in high humidity environments, grouting materials may absorb water and swell, causing structural damage. These problems seriously affect the long-term stability and safety of the project.
[0003] In recent years, with the continuous progress of materials science, researchers have begun to explore the use of composite salt materials as components of grouting materials. Composite salt materials are considered to be able to effectively improve the working performance of grouting materials in harsh environments due to their good chemical stability, corrosion resistance and excellent thermal stability. They can significantly improve the durability and impermeability of grouting materials, allowing them to maintain good performance under extreme climatic conditions.
[0004] However, despite the many theoretical advantages of composite salt grouting materials, they still face some challenges in practical application. Existing composite salt grouting materials have problems such as high complexity in preparation process, high cost, and difficulty in construction. These factors limit their widespread application in engineering. In order to overcome these obstacles, researchers are working hard to simplify the preparation process, reduce costs, and develop a formula for composite salt grouting materials that is easier to construct.
[0005] Through continuous research and innovation, it is expected that composite salt grouting materials with better performance, more economical cost and more convenient construction will be developed in the future, thus providing more reliable and efficient solutions for modern construction projects. Summary of the invention
[0006] In view of this, the present invention proposes a composite salt grouting material and a preparation method thereof, aiming to solve the problems existing in the prior art and provide a composite salt grouting material and a preparation method thereof with relatively low cost, simple preparation process and convenient construction.
[0007] The present invention provides a method for preparing a composite salt grouting material, comprising:
[0008] After mixing and stirring the fast-hardening sulphoaluminate cement, ordinary silicate cement and water at room temperature for 5-8 minutes, fly ash, slag powder, nano silicon powder and water are added, and the mixing and stirring is continued at room temperature for 7-10 minutes, and then the expansion agent and high-efficiency water reducing agent are added and mixed and stirred for 5-8 minutes to obtain a mixture;
[0009] Dissolve calcium chloride in water and stir until completely dissolved, pour the calcium chloride solution into the mixture and stir for 3-5 minutes, then add graphene oxide, titanium dioxide and water in sequence and continue stirring for 5-8 minutes to obtain a base material;
[0010] Slowly pour the modified methyl cellulose into the base material, stir for 3-5 minutes, and then let the mixed material stand for at least 10 minutes to obtain a mixed slurry;
[0011] The mixed slurry is naturally filtered to remove impurities, thereby obtaining the composite salt grouting material.
[0012] Preferably, the preparation method of the composite salt grouting material further comprises:
[0013] Rapid-hardening sulphoaluminate cement, ordinary silicate cement and water are mixed at room temperature, stirred at 300 rpm for 5-8 minutes, fly ash, slag powder, nano silicon powder and water are added, and the mixture is further mixed and stirred at room temperature and 200 rpm for 7-10 minutes, and then an expansion agent and a high-efficiency water reducing agent are added and mixed and stirred at room temperature and 100 rpm for 5-8 minutes to obtain a mixture;
[0014] Dissolve calcium chloride in water and stir until completely dissolved, pour the calcium chloride solution into the mixture, stir at 150 rpm for 3-5 minutes, add graphene oxide, titanium dioxide and water in sequence, and continue stirring at 300 rpm for 5-8 minutes to obtain a base material;
[0015] Slowly pouring the modified methyl cellulose into the base material, stirring for 3-5 minutes at a rotation speed of 200 rpm, and then allowing the mixed material to stand for at least 10 minutes to obtain a mixed slurry;
[0016] The mixed slurry is naturally filtered to remove impurities, thereby obtaining the composite salt grouting material.
[0017] Preferably, the weight ratio of the fast-hardening sulphoaluminate cement, ordinary Portland cement, high-efficiency water reducer, expansion agent, fly ash, slag powder, nano silicon powder, calcium chloride, graphene oxide, titanium dioxide and modified methyl cellulose is 95-100:48-50:2:4-5:18-20:13-15:1:0.5:0.2:0.3:0.5.
[0018] Preferably, the components of the rapid-hardening sulphoaluminate cement include calcium aluminate, silicon dioxide, calcium sulfate, iron oxide, magnesium oxide, sodium silicate, calcium carbonate and glass powder.
[0019] Preferably, the weight ratio of calcium aluminate, silicon dioxide, calcium sulfate, iron oxide, magnesium oxide, sodium silicate, calcium carbonate and glass powder is 45-50:10:20-25:5:2:1:5:7.
[0020] Preferably, the preparation method of the rapid-hardening sulphoaluminate cement comprises:
[0021] Calcium aluminate, silicon dioxide, calcium sulfate, iron oxide and magnesium oxide are mixed, and after stirring evenly, sodium silicate, calcium carbonate and glass powder are added, and at the same time, 8% of water of the total weight of all materials is added, and stirring is continued; the mixed wet material is crushed to control the particle size to be below 5 μm, and the crushed material is low-temperature dried to obtain the fast-hardening sulphoaluminate cement.
[0022] Preferably, the method for preparing the rapid-hardening sulphoaluminate cement further comprises:
[0023] Calcium aluminate, silicon dioxide, calcium sulfate, iron oxide and magnesium oxide are mixed, stirred at 500 rpm, sodium silicate, calcium carbonate and glass powder are added after stirring evenly, and water of 8% of the total weight of all materials is added at the same time, and stirring is continued at 300 rpm; the mixed wet material is crushed to control the particle size to be below 5 μm, and the temperature is controlled to be below 50° C. during the crushing process; the crushed material is low-temperature dried to obtain the fast-hardening sulphoaluminate cement.
[0024] The present invention also provides a composite salt grouting material, which is prepared according to the preparation method of the composite salt grouting material.
[0025] The present invention also provides an application of the composite salt grouting material in the field of construction.
[0026] The present invention also provides a building material, which comprises the composite salt grouting material according to claim 8.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The composite salt grouting material of the present invention exhibits excellent fluidity, and does not require additional water. The grouting performance can be optimized by introducing specific materials, effectively reducing material consumption, thereby reducing engineering costs. By adopting a combination of fast-hardening sulphoaluminate cement and ordinary silicate cement, the composite salt grouting material achieves rapid initial and final setting times, significantly improving construction efficiency. In addition, the added graphene oxide and titanium dioxide not only enhance the strength and durability of the grouting material, but also give the material self-healing properties, thereby extending its service life. By using modified methyl cellulose, the adhesion and crack resistance of the grouting material are further improved, ensuring that the structure after grouting is more stable and reliable. The preparation process of the present invention is simple and easy to operate, does not require complex equipment or high temperature environment, and is convenient for preparation and application at a variety of construction sites. The composite salt grouting material and its preparation method are not only suitable for the construction field, but can also be widely used in the grouting construction of bridges, tunnels, dams and other projects, showing broad application potential. DETAILED DESCRIPTION
[0029] The exemplary embodiments of the present disclosure will be described in more detail below. Although the exemplary embodiments of the present disclosure are shown below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0030] Example 1 Preparation of composite salt grouting material
[0031] 1. Raw materials (by weight)
[0032] 100 parts of fast-hardening sulphoaluminate cement; 50 parts of ordinary Portland cement; 2 parts of high-efficiency water reducing agent; 5 parts of expansion agent; 20 parts of fly ash; 15 parts of slag powder; 1 part of nano silicon powder; 0.5 parts of calcium chloride; 0.2 parts of graphene oxide; 0.3 parts of titanium dioxide; 0.5 parts of modified methyl cellulose.
[0033] Among them, the raw materials of rapid hardening sulphoaluminate cement include
[0034] 2. Preparation process
[0035] 1. Preparation process of rapid hardening sulphoaluminate cement
[0036] 1.1 Raw materials (by weight)
[0037] 45 parts of calcium aluminate (CaO·Al2O3); 10 parts of silicon dioxide (SiO2); 25 parts of calcium sulfate (CaSO4); 5 parts of iron oxide (Fe2O3); 2 parts of magnesium oxide (MgO); 1 part of sodium silicate (Na2SiO3); 5 parts of calcium carbonate (CaCO3); 7 parts of glass powder.
[0038] 1.2 Preparation process
[0039] Weigh all the raw materials to make sure they are dry and free of impurities. Next, add calcium aluminate, silica, calcium sulfate, iron oxide, and magnesium oxide to a high-speed mixer. Set the mixer to 500 revolutions per minute (rpm) and continue mixing for 10 minutes. This should be done at room temperature (20-25°C). It is important to ensure a smooth mix to prevent the materials from agglomerating.
[0040] Then, add the following additives: sodium silicate, calcium carbonate and glass powder to the mixed raw materials, and add 8% water based on the total weight of all materials. Adjust the mixing speed to 300 rpm and continue mixing for 5 minutes. The mixing process is also carried out at room temperature. Among them, sodium silicate helps to improve the fluidity of the material, while glass powder can enhance the strength of the material.
[0041] Next, the mixed wet material is sent to the ball mill for pulverization, and the pulverization time is set to 60 minutes. The particle size is controlled below 5μm to ensure the fineness of the material. During the pulverization process, the temperature must be strictly controlled below 50℃ to prevent overheating from damaging the performance of the cement.
[0042] Finally, the crushed material is dried at low temperature and packed into sealed bags to prevent moisture absorption. When storing, please choose a cool and dry environment.
[0043] 1.3 Performance Testing Experiment
[0044] In order to test the performance of the prepared rapid hardening sulphoaluminate cement, the following are the main test items and experimental procedures:
[0045] ①Coagulation time test
[0046] Method: Standard setting test equipment (such as Vicat apparatus) is used to determine the initial and final setting times of cement.
[0047] Sample preparation: Prepare slurry based on a water-cement ratio of 0.3.
[0048] Test temperature: maintained at 20±2℃.
[0049] Result standard: The initial setting time should not exceed 30 minutes, while the final setting time should be less than 1 hour.
[0050] ②Compressive strength test
[0051] Method: The compressive strength of cement at 1 day, 3 days and 7 days was determined using a compression testing machine.
[0052] Sample size: A prismatic specimen with a size of 40 mm × 40 mm × 160 mm was used.
[0053] Curing conditions: Curing should be carried out in a curing room with a temperature of 20±2℃ and a humidity exceeding 95%.
[0054] Loading speed: Apply load at a rate of 2400N / s.
[0055] Result standard: The compressive strength at 1 day old should reach or exceed 20MPa, while the compressive strength at 7 days old should reach or exceed 40MPa.
[0056] ③Flexural strength test
[0057] Method: The flexural strength of the sample was measured by a flexural testing machine.
[0058] Sample size: Use prismatic specimens with dimensions of 40 mm × 40 mm × 160 mm.
[0059] Test temperature: maintained at 20±2℃.
[0060] Loading speed: Apply force at a rate of 50N / s.
[0061] Result standard: The flexural strength at 7 days old should reach or exceed 7MPa.
[0062] ④Durability test
[0063] Methods: Cement specimens were immersed in sodium sulfate solution and their mass loss was evaluated after 28 days of immersion.
[0064] Sample size: A prismatic specimen with a size of 40 mm × 40 mm × 160 mm was used.
[0065] Solution concentration: Use 5% sodium sulfate solution.
[0066] Result standard: Quality loss should be controlled within 5%.
[0067] ⑤Results
[0068] The test results are shown in Table 1.
[0069] Table 1
[0070] Performance Indicators 1 day 3 days 7 days 28 days Initial setting time (min) 25 - - - Final setting time (min) 50 - - - Compressive strength(MPa) 22 35 42 55 Flexural strength(MPa) - - 7.5 10 Durability (%) - - - Mass loss 3.2%
[0071] It can be seen from the results in Table 1 that the prepared fast-hardening sulphoaluminate cement meets the performance requirements. The initial setting time of 25 minutes and the final setting time of 50 minutes are both within the specified 30 minutes and 1 hour, indicating that the cement has good fast-hardening properties. The compressive strength reaches 22MPa in 1 day, 35MPa in 3 days, 42MPa in 7 days, and as high as 55MPa in 28 days, all exceeding the standard requirements, indicating that the strength of the cement develops rapidly and the final strength is high. The flexural strength is 7.5MPa in 7 days and 10MPa in 28 days, which also meets the standard requirements, indicating that the cement has good flexural properties. In the durability test, the mass loss after 28 days was 3.2%, which is lower than the limit of 5%, indicating that the cement has good durability.
[0072] In summary, the various performance indicators of the prepared fast-hardening sulphoaluminate cement have met the design requirements and can be used in engineering applications that require rapid hardening and high early strength.
[0073] 2. Preparation process of composite salt grouting materials
[0074] Step 1: Cement Premix
[0075] Pour fast-hardening sulphoaluminate cement and ordinary Portland cement into a high-speed mixer at a weight ratio of 1:0.5, and add 10% of the total weight of all materials in water. Set the speed to 300 revolutions per minute (rpm) and continue stirring for 5 minutes. Keep the room temperature at 20-25°C. Make sure that the two cements are fully and evenly mixed to avoid agglomeration.
[0076] Step 2: Addition of mineral admixtures
[0077] Add fly ash, slag powder and nano silicon powder in sequence, and then add 10% of the total weight of all materials in water. Adjust the speed to 200 rpm and continue stirring for 7 minutes. Keep room temperature. Measures should be taken to prevent dust from spreading during the stirring process. It is recommended to use a closed mixer to ensure uniform distribution of the admixture.
[0078] Step 3: Add expansion agent and high-efficiency water reducer
[0079] Add the expansion agent and high-efficiency water reducer into the mixer in the specified proportion. Set the speed to 100 rpm (low speed) and continue stirring for 5 minutes. Set the temperature to 25°C. Observe the fluidity of the slurry during stirring to ensure that the effect of the high-efficiency water reducer is fully exerted.
[0080] Step 4: Preparation and addition of calcium chloride solution
[0081] Dissolve 0.5 parts of calcium chloride in 1 part of water and stir until completely dissolved. Slowly pour the calcium chloride solution into the blender while stirring. Set the speed to 150 rpm and continue stirring for 3 minutes. Keep the temperature at 25°C. Calcium chloride can accelerate the coagulation process of the material, so it should be added slowly and ensure even distribution.
[0082] Step 5: Adding Enhancer
[0083] Add graphene oxide and titanium dioxide in sequence, and add 2% water based on the total weight of all materials. Set the speed to 300 rpm and continue stirring for 5 minutes. Keep the temperature at 20-25°C. Titanium dioxide has a self-cleaning function, while graphene oxide can enhance the material's crack resistance. Make sure both are evenly distributed.
[0084] Step 6: Add thickener
[0085] Slowly pour the modified methyl cellulose into the blender. Set the speed to 200 rpm and continue stirring for 3 minutes. Keep the temperature at 25°C. The modified methyl cellulose will increase the viscosity and fluidity of the material, so make sure to stir evenly.
[0086] Step 7: Let the reaction stand
[0087] Let the mixed materials stand to ensure that the expansion agent reacts fully. Keep standing for 10 minutes. Temperature requirement: Maintain at 20-25℃. Note: Avoid disturbance during the standing period to ensure that the expansion agent acts fully, thereby improving volume stability.
[0088] Step 8: Filter and store
[0089] Operation: Use a 150 mesh screen to filter the mixed slurry naturally to remove impurities, and maintain the temperature at 20-25°C. The filtered slurry can be used immediately, and the unused slurry should be stored in a sealed container to prevent moisture evaporation.
[0090] Comparative Example 1 Preparation method of common composite salt grouting material
[0091] 1. Raw materials (by weight)
[0092] 60 parts of ordinary Portland cement; 20 parts of fly ash; 10 parts of slag powder; 5 parts of calcium sulfate; 3 parts of high-efficiency water reducing agent; 2 parts of expansion agent.
[0093] 2. Preparation steps
[0094] 1. Raw material mixing
[0095] Ordinary Portland cement, fly ash and slag powder were mixed in a predetermined ratio and stirred at a speed of 200 rpm for 5 minutes. The whole process was carried out at room temperature (20-25°C).
[0096] 2. Add auxiliary materials
[0097] Calcium sulfate, expansion agent and high-efficiency water reducer were added in sequence, and each material was stirred at 100 rpm for 5 minutes, ensuring that it was carried out at a constant temperature of 25°C. During the stirring process, the fluidity and uniformity of the mixture should be closely observed.
[0098] 3. Crushing and sieving
[0099] The mixed material is crushed until the fineness reaches less than 5 μm, and then sieved through a 150-mesh sieve.
[0100] 4. Storage
[0101] Store the sieved material in a sealed container in a dry and cool environment.
[0102] Test Example 1
[0103] In order to compare the performance of the improved composite salt grouting material (Example 1) and the ordinary composite salt grouting material (Comparative Example 1), the following tests were performed:
[0104] 1. Determination of coagulation time
[0105] Standardized setting time testing equipment is used to measure the initial and final setting time of concrete, ensuring that the test temperature is maintained at 20±2℃.
[0106] 2. Compressive strength assessment
[0107] The compressive strength of concrete at 1 day, 3 days and 7 days was evaluated by a compression tester. The samples used in the test were prismatic specimens with a size of 40 mm × 40 mm × 160 mm and were cured at a temperature of 20 ± 2 ° C and a humidity greater than 95%.
[0108] 3. Determination of flexural strength
[0109] The flexural strength of the sample was measured using a flexural testing machine. The test sample was also a prism specimen with a size of 40 mm×40 mm×160 mm, and the test was carried out at a temperature of 20±2°C.
[0110] 4. Durability assessment
[0111] The specimens were immersed in 5% sodium sulfate solution and after 28 days of immersion, their mass loss was measured to evaluate durability.
[0112] 5. Results
[0113] The test results are shown in Table 2-5.
[0114] Table 2
[0115] Material Type Initial setting time (min) Final setting time (min) Ordinary composite salt grouting material 60 120 Improved composite salt grouting materials 25 50
[0116] Table 3
[0117] Material Type Compressive strength(MPa) Maintenance days 1 day Ordinary composite salt grouting material 15 Improved composite salt grouting materials 22
[0118] Table 4
[0119] Material Type Flexural strength(MPa) Maintenance days 1 day Ordinary composite salt grouting material 3 Improved composite salt grouting materials 4.5
[0120] Table 5
[0121] Material Type Mass loss rate after immersion for 28 days (%) Ordinary composite salt grouting material 7 Improved composite salt grouting materials 3.2
[0122] As shown in Table 2-5, the improved composite salt grouting material is superior to the ordinary composite salt grouting material in both initial setting time and final setting time, which are shortened by 35 minutes and 70 minutes respectively. In terms of compressive strength, the improved composite salt grouting material has a compressive strength of 22MPa after 1 day of curing, which is 7MPa higher than the 15MPa of the ordinary composite salt grouting material, showing a faster strength development rate. Similarly, in terms of flexural strength, the improved composite salt grouting material has a flexural strength of 4.5MPa after 1 day of curing, which is 1.5MPa higher than the 3MPa of the ordinary composite salt grouting material. In the durability evaluation, the mass loss rate of the ordinary composite salt grouting material after immersion in 5% sodium sulfate solution for 28 days is 7%, while the mass loss rate of the improved composite salt grouting material is only 3.2%, indicating that the improved composite salt grouting material has better durability. In summary, the improved composite salt grouting material is superior to the ordinary composite salt grouting material in terms of setting time, compressive strength, flexural strength and durability, and is a grouting material with superior performance.
[0123] Test Example 2
[0124] In order to evaluate the performance of the grouting material under extreme climatic conditions, we conducted the following tests on Example 1 and Comparative Example 1:
[0125] 1. Compressive strength test under high temperature environment
[0126] The ambient temperature was set to 60°C to simulate the hot summer conditions.
[0127] The samples were subjected to compressive strength tests at 1 day, 3 days and 7 days.
[0128] The sample is a prism specimen with a size of 40 mm × 40 mm × 160 mm.
[0129] The high temperature curing condition is maintained at a constant temperature of 60°C.
[0130] 2. Compressive strength test under low temperature environment
[0131] The ambient temperature was set to -10 °C to simulate severe winter conditions.
[0132] The samples were subjected to compressive strength tests at 1 day, 3 days and 7 days.
[0133] The sample is a prism specimen with a size of 40 mm × 40 mm × 160 mm.
[0134] The low temperature curing condition is kept at a constant temperature of -10℃.
[0135] 3. High temperature / low temperature cycle durability test
[0136] The specimens were placed alternately in an environment of 60°C for 24 hours and in an environment of -10°C for 24 hours, which constituted one cycle.
[0137] After 10 cycles, the compressive strength and mass loss rate of the materials were measured.
[0138] The above tests are designed to fully evaluate the performance of grouting materials under extreme temperature changes.
[0139] The test results are shown in Tables 6-8.
[0140] Table 6
[0141] Material Type Compressive strength(MPa) Maintenance days 1 day Ordinary composite salt grouting material 12 Improved composite salt grouting materials 18
[0142] Table 7
[0143] Material Type Compressive strength(MPa) Maintenance days 1 day Ordinary composite salt grouting material 5 Improved composite salt grouting materials 10
[0144] Table 8
[0145] Material Type Compressive strength(MPa) Mass loss rate (%) Cycle times After 10 cycles After 10 cycles Ordinary composite salt grouting material 18 5 Improved composite salt grouting materials 30 2.5
[0146] It can be seen from Table 6-8 that under high temperature environment, the compressive strength of the improved composite salt grouting material is significantly higher than that of the ordinary composite salt grouting material. After one day of curing, the compressive strength of the improved composite salt grouting material is 18MPa, while that of the ordinary composite salt grouting material is only 12MPa. This shows that the improved composite salt grouting material has better mechanical properties under high temperature conditions.
[0147] In low temperature environment, the improved composite salt grouting material also showed better performance. After one day of curing, its compressive strength was 10MPa, while the ordinary composite salt grouting material was only 5MPa. This shows that the improved composite salt grouting material also has better compressive strength under low temperature conditions.
[0148] In the high temperature / low temperature cycle durability test, after 10 cycles, the compressive strength of the improved composite salt grouting material was 30MPa and the mass loss rate was 2.5%, while the compressive strength of the ordinary composite salt grouting material was 18MPa and the mass loss rate was 5%. This further proves that the durability and stability of the improved composite salt grouting material under extreme temperature changes are better than those of the ordinary composite salt grouting material.
[0149] In summary, the performance of the improved composite salt grouting material under extreme climatic conditions is significantly better than that of the ordinary composite salt grouting material, especially in terms of compressive strength and durability under high and low temperature environments. Therefore, the improved composite salt grouting material is more suitable for engineering applications under extreme climatic conditions.
[0150] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a composite salt grouting material, characterized in that: include: After mixing and stirring the fast-hardening sulphoaluminate cement, ordinary silicate cement and water at room temperature for 5-8 minutes, fly ash, slag powder, nano silicon powder and water are added, and the mixing and stirring is continued at room temperature for 7-10 minutes, and then the expansion agent and high-efficiency water reducing agent are added and mixed and stirred for 5-8 minutes to obtain a mixture; Dissolve calcium chloride in water and stir until completely dissolved, pour the calcium chloride solution into the mixture and stir for 3-5 minutes, then add graphene oxide, titanium dioxide and water in sequence and continue stirring for 5-8 minutes to obtain a base material; Slowly pour the modified methyl cellulose into the base material, stir for 3-5 minutes, and then let the mixed material stand for at least 10 minutes to obtain a mixed slurry; The mixed slurry is naturally filtered to remove impurities, thereby obtaining the composite salt grouting material.
2. The method for preparing the composite salt grouting material according to claim 1, characterized in that: Also includes: Rapid-hardening sulphoaluminate cement, ordinary silicate cement and water are mixed at room temperature, stirred at 300 rpm for 5-8 minutes, fly ash, slag powder, nano silicon powder and water are added, and the mixture is further mixed and stirred at room temperature and 200 rpm for 7-10 minutes, and then an expansion agent and a high-efficiency water reducing agent are added and mixed and stirred at room temperature and 100 rpm for 5-8 minutes to obtain a mixture; Dissolve calcium chloride in water and stir until completely dissolved, pour the calcium chloride solution into the mixture, stir at 150 rpm for 3-5 minutes, add graphene oxide, titanium dioxide and water in sequence, and continue stirring at 300 rpm for 5-8 minutes to obtain a base material; Slowly pouring the modified methyl cellulose into the base material, stirring for 3-5 minutes at a rotation speed of 200 rpm, and then allowing the mixed material to stand for at least 10 minutes to obtain a mixed slurry; The mixed slurry is naturally filtered to remove impurities, thereby obtaining the composite salt grouting material.
3. The method for preparing the composite salt grouting material according to claim 1, characterized in that: The weight ratio of the fast-hardening sulphoaluminate cement, ordinary silicate cement, high-efficiency water reducing agent, expansion agent, fly ash, slag powder, nano silicon powder, calcium chloride, graphene oxide, titanium dioxide and modified methyl cellulose is 95-100:48-50:2:4-5:18-20:13-15:1:0.5:0.2:0.3:0.
5.
4. The method for preparing the composite salt grouting material according to claim 1, characterized in that: The components of the fast-hardening sulphoaluminate cement include calcium aluminate, silicon dioxide, calcium sulfate, iron oxide, magnesium oxide, sodium silicate, calcium carbonate and glass powder.
5. The method for preparing the composite salt grouting material according to claim 4, characterized in that: The weight ratio of the calcium aluminate, silicon dioxide, calcium sulfate, iron oxide, magnesium oxide, sodium silicate, calcium carbonate and glass powder is 45-50:10:20-25:5:2:1:5:
7.
6. The method for preparing the composite salt grouting material according to claim 4, characterized in that: The preparation method of the rapid-hardening sulphoaluminate cement comprises: Calcium aluminate, silicon dioxide, calcium sulfate, iron oxide and magnesium oxide are mixed, and after stirring evenly, sodium silicate, calcium carbonate and glass powder are added, and at the same time, 8% of water of the total weight of all materials is added, and stirring is continued; the mixed wet material is crushed to control the particle size to be below 5 μm, and the crushed material is low-temperature dried to obtain the fast-hardening sulphoaluminate cement.
7. The method for preparing the composite salt grouting material according to claim 6, characterized in that: The preparation method of the rapid hardening sulphoaluminate cement also includes: Calcium aluminate, silicon dioxide, calcium sulfate, iron oxide and magnesium oxide are mixed, stirred at 500 rpm, sodium silicate, calcium carbonate and glass powder are added after stirring evenly, and water of 8% of the total weight of all materials is added at the same time, and stirring is continued at 300 rpm; the mixed wet material is crushed to control the particle size to be below 5 μm, and the temperature is controlled to be below 50° C. during the crushing process; the crushed material is low-temperature dried to obtain the fast-hardening sulphoaluminate cement.
8. A composite salt grouting material, characterized in that: The composite salt grouting material is prepared according to the preparation method of the composite salt grouting material according to any one of claims 1-7.
9. Use of the composite salt grouting material according to claim 8 in the field of construction.
10. A building material, characterized in that: The building material includes the composite salt grouting material according to claim 8.